Sekolah Alam Mekar Bakti Dalam Pembuatan Video Promosi Penunjang Informasi - Endang Sunandar; Miswanto Miswanto (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2019)
Information technology holds an important role in the world of education. Like Natural Blooming Tangerang Schools Act currently does not yet have the promotion. So the need for a promotional video, school of natural-shaped blooms in other schools of different service because of the way the lessons are in the wild. The results of this promotional video in order to be known by the public at large, so that the results of this promotional video can be developed in the community. The promotional video is very important if in create and disseminate in through social media.